Gladis monogatari - Sosa, Víctor (Poesía (Fondo de Cultura Económica (Mexico)), 2014)
Extended prose-poetic novel by Uruguayan-Mexican writer, presenting delirious compendium of realities and voices woven through existence of one woman through multiple ages and geographies. This work won Jaime Sabines International Poetry Prize in 2012.